Synedra sp. sebagai Mikroalga yang Ditemukan di Sungai Besuki Porong Sidoarjo, Jawa Timur - ISTI’ANAH, DINA; HUDA, MOCH. FAIZUL; LAILY, AINUN NIKMATI (Bioedukasi: Jurnal Pendidikan Biologi, 2015)
Microalgae in Sidoarjo Porong River is one component that can be used as bio-indicators of an imbalance in the ecosystem due to pollution load. Since the end of 2009, the River Porong Sidoarjo mud flow of water into which further aggravate the pollutant load to the Porong River. Water disposal Sidoarjo mud into the Porong River is thought to cause changes in the quality or increase water pollution. This study aims to determine phytoplankton found and to know the status of pollution in the river Besuki Porong Sidoarjo. Sampling was performed twice microalgae by using a plankton net and without plankton net or directly in September 2014. The results showed that the kind of microalgae found Synedra sp. The River Porong Sidoarjo. Synedra sp. is a type of algae from Chrysophyceae division that can live in almost every aquatic environment enough sunlight to sustain its activities. Environmental factors were measured at the time of sampling are: light intensity of 251 lux, the pH of 8, the water temperature was 29 °, and the air temperature at 32°C.